Identifying Functional Genes Influencing Gossypium hirsutum Fiber Quality - Dong, Chengguang; Wang, Juan; Yu, Yu; Ju, Longzhen; Zhou, Xiaofeng; Ma, Xiaomei; Mei, Gaofu; Han, Zegang; Si, Zhanfeng; Li, Baocheng; Chen, Hong; Zhang, Tianzhen (Frontiers in Plant Science, 2019)
Fiber quality is an important economic index and a major breeding goal in cotton, but direct phenotypic selection is often hindered due to environmental influences and linkage with yield traits. A genome-wide association study (GWAS) is a powerful tool to identify genes associated with phenotypic traits. In this study, we identified fiber quality genes in upland cotton (Gossypium hirsutum L.) using GWAS based on a high-density CottonSNP80K array and multiple environment tests. A total of 30 and 23 significant single nucleotide polymorphisms (SNPs) associated with five fiber quality traits were identified across the 408 cotton accessions in six environments and the best linear unbiased predictions, respectively. Among these SNPs, seven loci were the same, and 128 candidate genes were predicted in a 1-Mb region (± 500 kb of the peak SNP). Furthermore, two major genome regions (GR1 and GR2) associated with multiple fiber qualities in multiple environments on chromosomes A07 and A13 were identified, and within them, 22 candidate genes were annotated. Of these, 11 genes were expressed (log2(1+FPKM) >1) in the fiber development stages (5dpa, 10dpa, 20dpa and 25dpa) using RNA-Seq. This study provides fundamental insight relevant to identification of genes associated with fiber quality and will accelerate future efforts toward improving fiber quality of upland cotton.